Quadratic regression estimation of hybridized nanoliquid flow using Galerkin finite element technique considering shape of nano solid particles - Rahman, Mustafa Mutiur; Jamshed, Wasim; Devi. S, Suriya Uma; Ibrahim, Rabha W.; Pasha, Amjad Ali; Souayeh, Basma; Safdar, Rabia; Eid, Mohamed R.; Hussain, Syed M.; Tag El Din, El Sayed M. (Frontiers in Energy Research, 2022)
Because of its multivariate particle suspension approach, the developing class of fluid has a better level of stability as well as increased heat transfer. In this regard, hybrid nanofluid outperforms ordinary fluid and even well-known nanofluid. In a slick environment, we investigate its fluidity and heat transfer qualities. Nano-leveled particle morphologies, porousness materials, variable thermal conductivity, slippage velocity, and thermal radiative effects are all being studied. The Galerkin finite element method is a numerical methodology for numerically solving the governing equations (G-FEM). For this analysis, a Powell-Eyring hybrid nanofluid (PEHNF) flowing via a permeable stretchable surface is used, which comprises two types of nanoparticles (NP), copper (Cu), and titanium alloy (Ti6Al4V) dispersed in sodium alginate (C6H9NaO7). The heat transfer ratio of PEHNF (Ti6Al4V-Cu/C6H9NaO7) remained much greater than that of conventional nanofluids (Cu-C6H9NaO7), with a range of 43%–54%. When lamina particles are present, the thermal conductivity of the boundary layer increases dramatically, while spherical nanoparticles have the lowest thermal conductivity. As nanoparticles are added under their fractional sizes, radiative heat conductance, and flexible heat conductance, the system’s entropy increases. The flow system’s ability to transport mass decreases when molecule diffusivity decreases dramatically. This is theoretically related to a rise in Schmidt number against molecular diffusivity.